The Influence of Daily Conversations Students Toward Their Speaking Abilities at Ma’had Lughoh Gombong Layang Bandung - Hapsah, Hapsah Fauziah; Iin Nurul Inayah (Universitas Islam Tribakti Lirboyo, Kediri, 2024)
The activities are closely related to students' skill in education. And students' activities in daily conversation to upgrade students' speech skills. The initial study carried out by the researcher indicated that the students' activities in daily conversation were positive, and in fact their language skill in speech indicated a sufficient degree. Therefore, daily conversational activities are factors that determine their language skills in speech.The method used is the descriptive method and the data collection is obtained by observation, interview, questionnaire, tests and desk study, then the writer analyzes the data with partial analysis and correlational analysis. The steps used in this research are to determine the research method and methods, to determine the research complex and the sample, and to determine the data analysis, and these data are analyzed logically for qualitative data and statistical analysis of quantitative data. The fact that students' activities in everyday conversation and their relationship to their language skills in speech at the Linguistic Institute of the Department of Arabic Language Education at Gombong Layang Cipadung Bandung is unmodified.